SCREENING FOR SUDDEN CARDIAC DEATH IN ATHLETES: THE PSYCHOLOGICAL IMPACT OF BEING DIAGNOSED WITH POTENTIALLY LETHAL DISEASE. Issue 7 (11th March 2014) - Asif, I; Price, D; Fisher, L; Zakrajsek, R; Raabe, J; Bejar, M; Larsen, L; Rao, A; Harmon, K; Drezner, J
Abstract : Background: The purpose of cardiovascular screening in athletes is the identification of disorders at risk for sudden cardiac death. No study has assessed the experiences of athletes diagnosed with a serious cardiovascular condition. Objective: To determine the psychological impact of young athletes who are diagnosed with a potentially lethal cardiac condition. Design: Semi-structured interview. Setting: Young competitive US Athletes. Participants: 25 athletes (52% male, 80% Caucasian, median age 17.7) previously diagnosed (>6 months) with potentially lethal cardiac conditions (5 HCM, 8 WPW, 4 LQTS, 3 ASD, 2 SVT, 3 other) voluntarily participated. Assessment of risk factors: Athletes shared reactions and experiences regarding diagnosis, lifestyle implications, coping strategies, major concerns, and overall impact on psychosocial functioning. Main outcome measurements: Audio interviews were transcribed and analyzed using consensual qualitative research (CQR) to identify themes and sub-themes. Results: Athletes recalled anxiety, confusion, denial, and shock shortly after diagnosis. Disqualified collegiate athletes described prolonged emotional impact due to identity change, and had mixed emotions regarding participation in team activities in another role. Disqualified high school athletes were more accepting of their condition and chose to participate in lower intensity sports. Those undergoing simple corrective procedures depicted mentally overcoming their diagnosis quickly with little impact on daily life; however, individuals with cardiomyopathy or channelopathy had persistent reminders such as taking daily medication, monitoring HR during activity, and ensuring the presence of onsite defibrillators in case of cardiac arrest. Only a minority of athletes described emotional support mechanisms from medical programs. Diagnosis often led to new life purposes such as mentoring or coaching. Despite its impact, all athletes were appreciative and would undergo advanced cardiovascular screening again. Conclusions: College athletes and those with cardiac conditions requiring disqualification from sport are at greater risk of adverse psychological consequences. Improved support mechanisms from medical programs are needed to assist athletes diagnosed with a serious cardiac disorder.